Stochastic Reduced Order Modelling of a Fluid Structure Interaction System. (2016) - Remigius, W. Dheelibun; Lal, Hridya P.; Dubey, Jainendra K.; Godbole, Siddhesh M.; Gupta, Sayan; Sarkar, Sunetra
Abstract: Solution of large order fluid structure interaction (FSI) systems with parametric uncertainties demand intensive computational resources. The present study focusses on developing and implementing a novel stochastic reduced order model to resolve pressure induced oscillations of a disc-like structure as a generic fluid structure interaction system. Such models have applications in various heavy engineering systems, like turbo machinery industries. It is important to resolve the coupled dynamics, in order to avoid large oscillations and instabilities. The stochastic reduced order model uses a modal reduction approach together with sparse grid based polynomial chaos expansion (PCE) to truncate both the system degrees of freedom (dof) as well as the random modes. Further reduction in computational time is achieved by parallelization. Interfacing algorithms have also been developed that enable finite element (FE) modelling of the FSI system using commercial softwares and in-house developed codes.